2014
DOI: 10.5603/kp.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the levels of osteoprotegerin and the degree of coronary artery disease in patients with acute coronary syndrome and stable angina pectoris

Abstract: A b s t r a c tBackground: Osteoprotegerin (OPG), an inhibitor of osteoclastogenesis, has recently been under the spotlight in studies regarding the pathophysiology of atherosclerosis. Aim:To evaluate the value of serum OPG in the diagnosis and severity in patients with stable angina pectoris (SA) and unstable angina pectoris/non ST elevation myocardial infarction. Methods:This study involved 160 patients, SA (n = 65), acute coronary syndrome (NSTE-ACS; n = 65), and a control group (n = 30). Blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(50 reference statements)
2
6
2
1
Order By: Relevance
“…In our study, mean serum OPG levels were higher in patients with HF and CAD compared to CON ( p < 0.001). These results are in line with similar published findings [18,19,20].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, mean serum OPG levels were higher in patients with HF and CAD compared to CON ( p < 0.001). These results are in line with similar published findings [18,19,20].…”
Section: Discussionsupporting
confidence: 94%
“…They concluded that serum OPG levels had a long-lasting independent predictive power for all-cause mortality and cardiovascular death in these patients [18]. Aksu et al sustained that increased OPG could be accepted as a biomarker of coronary atherosclerosis [19]. In our study, mean serum OPG levels were higher in patients with HF and CAD compared to CON ( p < 0.001).…”
Section: Discussionsupporting
confidence: 48%
“…In contrast, in humans many authors suggest a positive association between serum OPG and atherosclerosis, arterial calcification, or CV disease [24]. High serum concentrations of OPG were correlated to the severity of peripheral arterial disease [25] and heart failure [26], unstable angina [27], acute myocardial infarction and risk of death [28]. Bjerre [29] reports that increased levels of OPG are not directly involved with the extent of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the control group, which consisted of healhy subjects, the OPG and OPG/RANK-L levels were significantly lower than those of both the ACS and the SAP groups ( 52 ). However, in another study involving patients with SAP, USAP, and non-STEMI, the OPG levels showed no correlation with the severity of CAD, which might be due to OPG and/or RANK-L polymorphism and some other possible genetic variations, but it may be accepted as an indicator of coronary atherosclerosis ( 53 ). Higher OPG levels detected in patients with ACS might be associated with increased cytokine levels.…”
Section: Osteoprotegerin: Structure Function and Metabolismmentioning
confidence: 99%